Associations between air pollution, climate factors and outpatient visits for eczema in West China Hospital, Chengdu, south‐western China: a time series analysis. (22nd December 2017) - Li, A.; Fan, L.; Xie, L.; Ren, Y.; Li, L.
Abstract: Background: Eczema is one of the most common inflammatory dermatoses that can be provoked as a result of external and internal factors. With dense population and rapid economic development of China, air pollution is still a serious problem and the prevalence of eczema has been elevating. Objective: To determine the association and lagged effects between environmental factors and the outpatient visits for eczema. Methods: Data of daily outpatient visits for eczema at the clinics of dermatology in West China Hospital within the last 5 years were collected. Data of environmental factors of Chengdu during the same period, including temperature, relative humidity, barometric pressure, wind speed and air pollutants concentrations like sulphur dioxide (SO2 ), nitrogen dioxide (NO2 ) and particular matter (PM10 ), were gathered. The distributed lag nonlinear model was used to statistically examine the relationship between eczema and environmental factors and their lagged effects. Results: Correlation analysis showed that eczema outpatient visits were positively correlated with the air pollutants and were negatively correlated with relative humidity. The barometric pressure and wind speed influenced the outpatient visits in association with air pollutants. Conclusion: This study provides evidence that environmental factors like relative humidity and multiple air pollutants influence the incidence and prevalence of eczema and have lagged effects.